KINERJA APARATUR SIPIL NEGARA (ASN) DI KANTOR KECAMATAN PALU UTARA KOTA PALU (STUDI TENTANG PELAYANAN ADMINISTRASI KEPENDUDUKAN) - Tahir, Ulul Amri; Mustari, Hasanuddin; Nurhannis, Nurhannis (Katalogis, 2019)
The reseach intends to identify the permofance of civil servant in the subdistrict office of North Palu in providing public administration service. This is acase study using descriptive qualitative type with 14 informants. Samplewas selected through purpusive sampling.Data were collected through observation , interview , and documentation.TheÂ  result of this research shows that the perfomance of civil servant in the sub-district office of North Palu has not optimal yet due to the perfomance theory as stated by TR. Mitchel in Sedamaryanti : work qualtiy , accuracy , initiative , abilty , and comunication generally does not run well. It caused by the lack of facilities and infrastructure and weak coordination of the leader or the opposite , lack of training and discipline caused the non optimal work professionals.Â